Relationships between personality traits and attachment to parents and peers, with delinquent behavior among adolescents in Tehran, Iran - Rouzegari, Shahrzad (2013)
The study aims to examine the relationships between personality traits and attachment with parents and peers with self-reported delinquency, among Iranian adolescents in Tehran, Iran. The study concentrated on delinquent behaviors reported by the adolescents themselves. A total of 315 adolescents (165 girls and 150 boys) aged between 12 to 18 years old selected from public guidance and high schools of Tehran, Iran were involved in the study. The research design of study was correlational, cross-sectional survey and multi-stage cluster sampling technique was used to choose the respondents. Students who had broken the rules of schools at least one time (according to Tehran General Organisation of Education, 2011) were selected as respondents. Respondents were asked to answer the self-questionnaires booklet which included of age, gender, number of siblings, area of living, parent`s age, job and education, and the monthly income of the family. Personality traits (Psychoticism, Extraversion, and Neuroticism) as independent variables were measured with Junior Eysenck personality Questionnaire (JEPQR-S-, Corulla, 1990), attachment to parents and peers were measured with (IPPA-R), Inventory of Attachment to Parents and Peers (Greenberg & Armsden, 1987), as mediating factor, and self-reported delinquency was assessed by an Adapted Version of Self-reported Delinquency Questionnaire (Carroll, 1996; Mak, 1993), as the dependent variable in this study. The results of the study revealed a positive significant correlation between Psychoticism (r=.151), Extraversion (r=.238) and Neuroticism with delinquency (r=.114) among respondents. Attachment with mother mediated the relationships between personality traits and school misdemeanors and attachment with father mediated the relationship between personality traits and school misdemeanors and physical aggression offences. However, the mediation effect of attachment with peers on the relationship between psychoticism, extraversion and neuroticism with delinquency was not established. The findings of the current study indicated that despite having a strong attachment to parents and peers, adolescents may involve in delinquent behavior because of their personality characteristics like being high in psychoticism, extraversion and neuroticism. According to the results of current study, the personality model of Hans Eysenck is a useful method to describe delinquent behavior in adolescents. Adolescents who are high in psychoticism, extraversion and neuroticism are more likely to be involved in delinquency. Besides, social control theory of Hirschi is a proper ecological model which indicates that having good relationship with mother and father decrease the probability of juveniles „involvement in physical aggression and school misdemeanors offences. The results have a number of important implications for parents, teachers, schools, psychologists, ministry of education, and above all, the social aids who deal with delinquent adolescents in correction and rehabilitation centers, to develop an accurate intervention program for adolescents at high risk of delinquency. Findings of current research will help to early identification of students who were reported as high level of involvement in delinquent behaviors, to plan immediate comprehensive program to prevent them from involving in more serious problems in future.